2022
DOI: 10.1002/asia.202101428
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Dry Reforming of Methane Catalysed by Atomically‐Dispersed Ni over Ceria‐Upgraded Boron Nitride

Abstract: Dry reforming of methane (DRM) is a very promising protocol to mitigate the greenhouse gases by making use of CO 2 and CH 4 to produce valuable syngas. Nibased catalysts exhibit high activity and low cost for DRM, but suffer from inferior stability because of serious carbon deposition. Herein, we proposed atomically dispersed Ni supported by ceria-upgraded boron nitride whose specific activity exceeds that of boron nitride-supported Ni by 3 times. The results of temperature-programmed surface reaction show cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, metal–BN interfaces can be constructed with the expectation of facilitating MDR. Most recently, we found that the interface of Ni–BN could enhance the coke resistance of Ni catalysts. , However, the sintering of Ni particles still happened over the bare BN surface. The metal oxide was introduced to further improve the sintering resistance of the Ni/BN catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, metal–BN interfaces can be constructed with the expectation of facilitating MDR. Most recently, we found that the interface of Ni–BN could enhance the coke resistance of Ni catalysts. , However, the sintering of Ni particles still happened over the bare BN surface. The metal oxide was introduced to further improve the sintering resistance of the Ni/BN catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in recent literature, the Ni species tend to agglomerate into large particles on h-BN due to the hydrophobic properties of pristine BN. 42 In this work, the introduction of CeO x can provide new sites for Ni species anchoring.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al have also demonstrated the coke-resistant character of an atomically dispersed metal catalyst for high-temperature dry reforming of methane (DRM). 37,47 The initial activity and stability of the atomically dispersed Ni catalyst against coke formation were promising. However, single-atomic Ni sites easily agglomerated into large metal particles during the high-temperature DRM reaction, making them susceptible to coke formation and resulting in rapid deactivation.…”
Section: Coke-resistant Catalystsmentioning
confidence: 99%
“…Zhang et al have also demonstrated the coke‐resistant character of an atomically dispersed metal catalyst for high‐temperature dry reforming of methane (DRM) 37,47 . The initial activity and stability of the atomically dispersed Ni catalyst against coke formation were promising.…”
Section: Coke‐resistant Catalystsmentioning
confidence: 99%